Residual effect of fertilization with micronutrients under "cerrado" soil on soybean yield and leaf contents - Silva, Ady Raul da; Andrade, José Maria V. de; Peres, José Roberto R. (Pesquisa Agropecuaria Brasileira, 2014)
The residual effect of micronutrients applied in virgin soils of "cerrado" for wheat was studied in soybean yield and leaf content of Cu, Fe, Mn, Zn, Ca, Mg, P, K and N, in two years 1980/81 and 1981/82. Only zinc increased the yield: 92.7% and 29.4% in the first and in the second crop respectively, equivalent to 908 and 1,097 kg/ha. The leaf analysis was the only way to identify the zinc deficiency without check plots. There were largo differences in yield and the leaf contents of micronutrients, in the two years. There were positive correlations between: yield and Zn, K, N total, nodule weight, plant weight, K and Zn, Mg and Ca, Cu and K; negative correlations: yield and Mn, yield and Mg, Zn and Mn, Mg and K, Mg and Zn, Fe and K.